Accurate analysis method of network element performance and service data characteristics - Xuanyu GUO (Dianxin kexue)
The performance of telecommunication network was usually analyzed by the KPI of network management system.If there was something wrong with the KPI,it needed the network optimization personnel to position problems.The efficiency of analyzing result depended on the quality of the network optimization personnel.Meanwhile,the analysis of data performance was rough estimated.As the unified deep packet inspection could show out the smaller granularity of the service status and channel quality,the analysis method of service data and node performance was discussed.By data slice and data association of control plane XDR and user plane XDR,the performance was analyzed with smaller granularity to show the quality of the network and the experience of users.So the user experience was showed out by different applies and services with different scenes,and the data characteristics of the XDR were more clearly.Finally,it improves the efficiency of network optimizing,the user feeling and the capability of data realization.